Fundamentals of Information Systems - Polle, Torsten; Ripke, Torsten; Schewe, Klaus-Dieter (Springer US, 1999)
Fundamentals of Information Systems contains articles from the 7th International Workshop on Foundations of Models and Languages for Data and Objects (FoMLaDO '98), which was held in Timmel, Germany. These articles capture various aspects of database and information systems theory: identification as a primitive of database models deontic action programs marked nulls in queries topological canonization in spatial databases complexity of search queries complexity of Web queries attribute grammars for structured document queries hybrid multi-level concurrency control efficient navigation in persistent object stores formal semantics of UML reengineering of object bases and integrity dependence . Fundamentals of Information Systems serves as an excellent reference, providing insight into some of the most challenging research issues in the field
Keywords: Computer Science; Data Structures, Cryptology and Information Theory; Information Storage and Retrieval; IT in Business; Computer Science, general; Computer science; Information technology; Business / Data processing; Data structures (Computer science); Information storage and retrieval; Datenbankverwaltung; Informationssystem; Konferenzschrift -- 1998 -- Timmel